Manajemen Pembelajaran Pendidikan Agama Islam Di Taman Kanak-Kanak Islam Terpadu Di Masa Pandemik Covid 19 - Suryati, Sri; Baidi, Baidi (JOEAI (Journal of Education and Instruction), 2021)
This study aims to determine the implementation of Islamic religious education learning management, supporting factors, obstacles and solutions in the implementation of Islamic religious education learning management at TKIT An Najah Jatinom Klaten during the Covid 19 pandemic. This study uses a qualitative research approach. The research subjects were the head of the kindergarten, while the informants were the teachers. Data analysis uses data collection, data reduction, data presentation and drawing conclusions. The results of the study obtained several things regarding; 1) The management of Islamic religious education learning at TKIT An Najah Jatinom Klaten during the pandemic has been able to run well; 2) The moral factor in the form of the spirit of carrying out the mandate of the teachers in the task of being a supporting factor in the management of Islamic religious education learning at TKIT An Najah Jatinom Klaten during the pandemic period; 3) The inhibiting factors are difficult internet signals, limitations of parents in the use of technology devices, busy work of parents, children do not like being guided by their parents, or prefer to be guided by teachers; 4) The solution is that the parents are given assistance to buy credit, to make home visits more efficient, groups are made, private tutoring is held by the teacher, or teachers also make Islamic education lessons with video calls. In conclusion, the implementation of Islamic Religious Education learning management has been able to run well, with the support and trust of the teachers in carrying out their duties, while the inhibiting factor for the implementation of learning is the difficulty of internet signals. Keywords: Management, Learning, Islamic Religious Education, Pandemic Period